Prevalence of Parkinson's disease among adults aged 45 years and older in China: a cross-sectional study based on the China health and retirement longitudinal study - Detao Meng; Jiayu Wu; Xinyu Huang; Xiaoxiao Liang; Boyan Fang (BMC, 2024)
Abstract Background In recent decades, China has experienced a rapid increase in the number of elderly individuals and life expectancy, as well as industrialization, which is associated with an increased prevalence of Parkinson's disease (PD). However, inconsistent results have recently been reported. Therefore, this study aimed to investigate the prevalence and distribution characteristics of PD among individuals aged 45 years and older. Methods Using data from the China Health and Retirement Longitudinal Study (CHARLS), we attempted to estimate the prevalence of PD and its distribution characteristics among 19,034 individuals aged 45 years and older residing in 446 communities/villages within 27 provinces/autonomous regions/municipalities in mainland China. Cases were established based on a doctor's previous diagnosis. Crude and age-adjusted prevalence rates were calculated and stratified by age, sex, area of residence, education level, marital status, and geographic region. Logistic regression models were used to identify risk factors associated with PD. Results We identified 178 patients with PD among 19,034 residents aged 45 years and older. The crude prevalence was 0.94%, and the age-adjusted prevalence was 0.82% for individuals aged 45 years and older. The prevalence of PD increased with age (P < 0.001). No significant differences were found in terms of sex, area of residence, or education level. Stratified by geographic region, the prevalence of PD was greater in North and Northwest China and lower in southern China (p < 0.001). Multiple regression analyses showed that age was a significant risk factor for PD. Conclusion The prevalence of PD increased with age in the Chinese population.